Study of Secondary Bacterial Infections Among the Patients with Cutaneous and Mucocutaneous Leishmaniasis in Thamar City- Yemen. - Al-Asbahi, Amin Abdu; Al- shahethi, Mohammed Ali (Journal of Amran University, 2022)
The main objective of this study was to determine the how common secondary bacterial infections that are isolated from patients with cutaneous and mucocutaneous leishmaniasis in Thamar City- Yemen. This study included patients admitted to the Skin Disease Unit and the Thamar General Hospital lab between August 2020 and January 2021. Clinical samples were examined using standard parasitological and bacteriological methods. The study included 81 patients, and leishmania was found in 60 (74 percent) of them. Bacterial infections had also infected 60 cases. The most common secondary infection bacterial causative agents found in this study were 30 isolates (38%) of kocuria spp out of the total number 79 bacterial isolates, 28 (35.4%) isolates of Bacillus spp., 12 (15.2%) isolates of P. aeruginosa and 9 (11.4%) isolates of S. aureus. Sensitivity testing revealed that 16% of S. aureus was resistant to Azithromycin, 35% of Kocuria spp. were resistant to Cefotaxime and 30% were resistant to Ceftriaxone, 36% of Bacillus spp. were resistant to Azithromycin, and 20% were resistant to Ceftriaxone, 8.3% of P. aeruginosa were resistant to Azithromycin and 10% were resistant to Ceftriaxone. The majority of isolates (35–50%) were sensitive to Ofloxacin and Ciprofloxacin. The recent article's results indicate that bacterial infections are still a significant problem in patients with cutaneous leishmaniasis in Yemen, and should be considered when treating these patients.